The Implications of Cross-Docking in the Manufacturing Sector of Pakistan - Khan, Habibullah; Hussainy, Syed Karamatullah; Khan, Kamran; Khan, Eesar; Shareef, Mohammad; Tariq, Shaista (International Journal of Supply Chain Management, 2017)
Abstract - Purpose of the study is to find out the role of cross-docking in FMCG sector of Pakistan. Research will be helpful to find out the benefits, risks, benefits and challenges for implementing the cross-docking in organizations. The researchers have gathered the interview from twelve supply chain managers working in the manufacturing sector of Pakistan. The study can be useful for the organizations adopting the cross-docking strategy especially in the uncertain countries. The result shows that cross-docking leads to improve the customer services and helps to achieve cost-effectiveness. It can improve the lead time tremendously but labor cost does not get reduced in cross-docking. Cross-docking may lead to increase the risk of uncertainties, chances of pilferages and damages. Keywords: Cross-docking, warehouse, pilferage, lead time, cost, customer satisfaction, customer services, uncertainty, damages, safety stock